Application of Teaching Materials Writing Summary Folk Stories "Malin Kundang" Using YouTube Video for Students at Al Misbah Islamic Middle School - Delly Yanti, Vitania Barantika; Risnawaty; Widayatul Jannah; Sutikno; Rahmat Kartolo (International Journal of Educational Research Excellence (IJERE), 2026)
This study examines the application of YouTube videos as teaching materials in learning to write summaries of the folk tale "Malin Kundang" for eighth-grade students of SMP IT Al Misbah Pematang Kuala. The study used a qualitative descriptive approach with a case study method, involving 20 students as research subjects. Data were collected through learning artifacts in the form of story summaries written by students, observations of the learning process, and learning documentation. Analysis was carried out multidimensionally covering narrative structure, linguistic quality, paraphrase originality, and textual coherence. This effectiveness is explained through the Cognitive Theory of Multimedia Learning (Mayer, 2021), which states that dual-channel processing (visual and auditory) produces a richer, integrated mental representation than single-channel processing. YouTube videos facilitate the modality transformation from oral-visual input to textual output, resulting in more authentic paraphrasing than written text-based learning, which tends to encourage copy-pasting. Individual variations in summary length (120-200 words), opening type (5 types), and storytelling focus (3 perspectives) reflect meaningful construction and learner agency, not weakness. This research reconceptualizes YouTube videos from an entertainment platform to a cognitive tool that facilitates deep learning and skill development. Further research with a quasi-experimental design, a larger sample size, a longitudinal approach, and a think-aloud protocol is recommended for stronger validation. This research contributes to the empirical validation of CTML in the context of EFL writing, the extension of paraphrasing and modality transformation theories, and the development of a multidimensional qualitative descriptive analysis framework for assessing summary quality. The findings confirm that YouTube videos, when integrated with a structured learning design, can be an integral component of Indonesian language learning that enhances digital native student engagement, facilitates higher-order thinking, and minimizes plagiarism through authentic paraphrasing